Vimentin Suppresses Inflammation and Tumorigenesis in the Mouse Intestine - Wang, Linglu; Mohanasundaram, Ponnuswamy; Lindström, Michelle; Asghar, Muhammad Nadeem; Sultana, Giulia; Misiorek, Julia O.; Jiu, Yaming; Chen, Hongbo; Chen, Zhi; Toivola, Diana M.; Cheng, Fang; Eriksson, John E. (Frontiers in Cell and Developmental Biology, 2022)
Vimentin has been implicated in wound healing, inflammation and cancer, but its functional contribution to intestinal diseases is poorly understood. To study how vimentin is involved during tissue injury and repair of simple epithelium, we induced colonic epithelial cell damage in the vimentin knockout (Vim-/-) mouse model. Vim-/- mice challenged with dextran sodium sulfate (DSS) had worse colitis manifestations than wild-type (WT) mice. Vim-/- colons also produced more reactive oxygen and nitrogen species (ROS/RNS), possibly contributing to the pathogenesis of gut inflammation and tumorigenesis than in WT mice. We subsequently describe that CD11b+ macrophages served as the mainly cellular source of ROS production via vimentin-ROS-pSTAT3-IL-6 inflammatory pathways. Further, we demonstrated that Vim-/- mice did not develop colitis-associated cancer (CAC) model upon DSS treatment spontaneously, but had increased tumor numbers and size in the distal colon in the azoxymethane (AOM) / DSS model comparing with WT mice. Thus, vimentin has a crucial role in protection from colitis induction and tumorigenesis of the colon.